064 Effects of dietary supplementation of β-mannanase on immune responses in nursery pigs. (1st August 2017) - Jang, K.; Kim, K.; Kim, S.; Kim, J.; Kim, B.; Park, S.; Lee, J. J.; Lee, J. H.; Kim, S. W.; Song, M.
Abstract: Feed enzymes targeting nonstarch polysaccharides (NSPases) can bring positive effects for pigs through improving nutrient digestion and utilization by releasing nutrients trapped in nonstarch polysaccharides such as mannans and xylans. However, little information about NSPases effects on pig health and immunity is available. The objective of this study was to evaluate effects of dietary supplementation of β-mannanase on immune responses in newly weaned pigs. A total of 72 weaned pigs (5.9 ± 0.5 kg BW and 21 d old) were randomly allotted to 4 dietary treatments (3 pigs/pen and 6 replicates/treatment) in a randomized complete block design (block = BW). Dietary treatments were in a factorial arrangement: 0 or 0.05% β-mannanase (CTCBIO Inc., Seoul, Korea) and 0 or 0.05% cocktail enzyme (combination of xylanase, α-amylase, protease, β-glucanase, and pectinase; CTCBIO Inc.). Pigs were fed for 6 wk using a 2-phase feeding program with each phase of 3 wk. Dietary treatments did not include antibiotics, fish meal, blood plasma, and zinc oxide. Blood samples were collected from randomly selected 2 pigs in each pen on d 1, 2, 3, 7, and 14 after weaning. Measurements were cortisol, tumor necrosis factor-β (TNF-β), transforming growth factor-β (TGF-β), C-reactive protein (CRP), and IgG, IgM, and IgA by ELISA. Data were analyzed using PROC MIXED of SAS. The statistical model included effects of 2 factors and their interaction as fixed effects and block as a random effect. Supplemental β-mannanase decreased ( P < 0.05) cortisol on d 14 (3.29 vs. 6.40 ng/mL), TNF-β on d 3 (0.74 vs. 1.06 ng/mL) and 7 (0.75 vs. 1.18 ng/mL), TGF-β on d 2 (1.27 vs. 1.62 ng/mL), and CRP on d 7 (4.02 vs. 4.87 ng/mL) and 14 (3.44 vs. 4.58 ng/mL) after weaning and increased ( P < 0.05) IgG on d 7 (27.2 vs. 18.5 mg/mL) after weaning compared with diets without β-mannanase, but there were no β-mannanase effects on IgM and IgA. No effects of cocktail enzyme and interaction between β-mannanase and cocktail enzyme were found for all measured variables. In conclusion, dietary supplementation of β-mannanase in nursery diets reduced stress and inflammation indicators and increased IgG in nursery pigs.